THEORETICAL METHODOLOGICAL ISSUES OF STUDYING ALOUDDIN ATTOR'S SCIENTIFIC HERITAGE - Эркин Раҳматов (American Journals, 2023)
It is known from history that Muslims of the world are very interested in the shrines of the Pirs of the Naqshbandi order, like many shrines in our country. However, there are great scholars, pirs, and murshids belonging to this series, whose life, spiritual heritage, and contribution to the life of the society have not been sufficiently scientifically substantiated yet.